Preparatory process tourists conductors on the pre basic training - Горбонос-Андронова [Elena Gorbonos-Andronova], Олена Русланівна; Микитчик [Olga Mikitchik], Ольга Сергіївна (Slobozhanskyi Herald of Science and Sport, 2013)
The paper analyzes the features of construction of the preparatory process water tourists during pre- basic training, tools used in the training process. A study of scientific and methodological literature on the methodology for water tourist. A questionnaire survey of coaches and managers of boating sports clubs, by the construction of the preparatory process of the athletes. The features of the preparation of water-tourists during pre- basic training. Found that to date there is no universal method of the physical qualities of athletes involved in boating. The ways of overcoming the problems.